Characterization and Stage-Dependent Lineage Analysis of Intermediate Progenitors of Cortical GABAergic Interneurons - Esumi, Shigeyuki; Nasu, Makoto; Kawauchi, Takeshi; Miike, Koichiro; Morooka, Kento; Yanagawa, Yuchio; Seki, Tatsunori; Sakimura, Kenji; Fukuda, Takaichi; Tamamaki, Nobuaki (Frontiers in Neuroscience, 2021)
Intermediate progenitors of both excitatory and inhibitory neurons, which may help regulate neuronal numbers in the adult brain, were recently identified. However, the generation of intermediate progenitors of GABAergic inhibitory neurons (IPGNs) has not been studied in detail. Here, we characterized the spatiotemporal distribution of IPGNs in mouse cerebral cortex. IPGNs generated neurons during both embryonic and postnatal stages, but embryonic IPGNs were more proliferative. Our lineage tracing analyses showed that the final laminar distributions of embryonic and postnatal IPGNs differ in adult brain. We also found that although embryonic IPGNs were broadly distributed in the cerebral cortex and the medial ganglionic eminence, most of the IPGNs were observed in the subventricular zone of the medial ganglionic eminence. Taken together, our data indicate that the broadly located IPGNs during embryonic and postnatal stages exhibit different properties.